THE IMPLEMENTATION OF MODEL OF STUDENT SPORT COACHING AND DEVELOPMENT IN PUBLIC POLICY PERSPECTIVE, MANADO NORTH SULAWESI 2010 (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
The implementasion of model for student sport coaching in North Sulawesi still face a lot of problems either conceptually or factually. The problems are: the weakness of recruiting strategies, the absence of long-term guidance for qualified athletes, less distributed international or national standardized coach, the lack of facilities and infrastructure, the disintegration of stakeholders policy, poor organization and management, the lack of competition, the budget has been inadequate, and the local government are quite careless. If the problems are not immediately handled, it is afraid that the of student sport guidance and training will bring negative impact more complexly. That is why UU No. 3 Year 2005 about, National Sport Systems. This research studies the public implementation for students sport coaching. The research focus on: translation ability, that is ability of policy subjects to comprehend of students sport guidance policy, organizations and management, support of central and local government budgeting, and sport facilities and infrastructures. The techniques of collecting data are participatory observation, in-depth interview, document investigation, and triangulation. The obtained data are analyzed qualitatively by using steps as follows 1) data reduction, 2) data display, and 3) data conclusion.The findings of the research are as follows: 1) from policy initiation perspective, the process of decision-making is not objectively decided by need analysis to cope with public problems, 2) the translation ability are effective enough to manage of students sport guidance, 3) the organization and management as supporter system to a policy implementation tend to be less effective in facilitating the implementation function policy of students sport guidance, 4) the budgeting still tends to be less directional and proportional for each activity unit, and 5) facilities and infrastructures is quite adequate but they are lack of care and maintenance.Based on the result of research, the researcher recommends: 1) the implementation model for students sport coaching, 2) translation ability are adapted from education background and experience, 3) the organization and management are reorganized by encouraging schools as central of student sport guidance in local, 4) government needs to invite private sectors, BUMN, and banking in budgeting of student sport guidance by construing the regulation through legislation, and 5) the availability of standard facilities and infrastructure are conducted completed with maintenance and reparation.